2022-VA-1275-ESGO Agressive angiomyxoma of the pelvis and vagina: a robotic and vaginal combined approach. (20th October 2022) - Luzarraga, Ana; Pérez-Benavente, Asunción; Conesa, Vicente Bebia; Cabrera, Silvia; Sanchez Iglesias, Jose Luis; Gomez-Hidalgo, Natalia Rodriguez; Moreno, Antonio Gil
Abstract : Introduction/Background: Aggressive angiomyxoma (AA) is a rare mesenchymal tumor, typically arising in the soft tissue of the pelvis and perineum 1, with local aggressive behavior and frequent local recurrence. Surgical excision is the standard treatment 2 . Methodology: We report the case of a 47-year old woman diagnosed with a pelvis and perineum AA. Magnetic resonance imaging revealed a 9cm infiltrative mass at the level of the lateral wall of the left introitus, extending to the left infravesical space, lateral wall of the vagina and anal sphincter, infiltrating the left levator ani muscle and ischiorectal fossa. A surgical treatment was performed. Results: First, a robotic approach with standard five-port placement configuration was used. Surgical strategy initially consisted in the development of the lateral avascular spaces of the left pelvis: lateral and medial paravesical spaces, lateral pararectal space and left obturator fossa. The first maneuver consisted in the detachment of the tumor from the obturator fossa and left lateral wall of the bladder. Then, development of the Retzius space up to the bladder neck was realized to identify the pre-vesical portion of the tumor. The use of intravenous ICG helped to identify the anatomical plane for the detachment of the tumor from the bladder. A technical difficulty for the excision of the AA is its soft consistency, making it easy to confuse with soft fatty tissues of the pelvis and making it difficult to obtain negative pathologic margins. Next, a vaginal approach with a longitudinal incision was performed, enabling the identification of the ischiatic tuberosity, ischiocavernosus, bulbocavernosus, and perineum transversus muscles. Ischiorectal fossa was developed and the tumor exteriorized. Detachment of the AA from the lateral wall of the vagina and rectum enabled the excision of the surgical specimen. Conclusion: The pathologic analysis revealed positive margins. The patient was discharged four days later.